2018
DOI: 10.1007/s40870-018-0148-4
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Mixed Silica Micro-nanoparticles on Compressive Dynamic Stiffness and Damping of Epoxy Adhesive

Abstract: Dynamic stiffness and damping of epoxy adhesives are critical for ensuring the safety, reliability, and comfort of structures subjected to vibrations and impact loads. This study conducts split Hopkinson pressure bar (SHPB) tests to investigate the synergistic effects of silica micro-nanoparticles on these critical properties. Micro-nanoparticle content and composition ratio purity are varied at 2, 5, and 10% by weight (wt%) and from 0% (pure microparticles) to 100% (pure nanoparticles), respectively. Positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, an in vitro study has reported that the bigger nanoparticles promote the cellular uptake of the smaller nanoparticles with a total uptake increase of particles in the cells [ 32 ]. Additionally, some physicochemical properties could have changed when micro-particles mixed with nanoparticles [ 29 , 34 , 54 , 55 ], which may also have affected their toxicities. The increased uptake of the “more-toxic” PS50 and the total particle count may be the cause of the enhanced toxicity in the mixture of PS50 and PS500.…”
Section: Discussionmentioning
confidence: 99%
“…However, an in vitro study has reported that the bigger nanoparticles promote the cellular uptake of the smaller nanoparticles with a total uptake increase of particles in the cells [ 32 ]. Additionally, some physicochemical properties could have changed when micro-particles mixed with nanoparticles [ 29 , 34 , 54 , 55 ], which may also have affected their toxicities. The increased uptake of the “more-toxic” PS50 and the total particle count may be the cause of the enhanced toxicity in the mixture of PS50 and PS500.…”
Section: Discussionmentioning
confidence: 99%
“…In polymer‐based composites, ceramics are selected as fillers because they have properties that can strengthen the polymeric matrix. One such ceramic is silica (SiO 2 ), which is abundant and has a relatively high specific tensile strength . Furthermore, silica has several types of polymorphs, including quartz and cristobalite .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the stress-strain curve shown in Fig. 6 does not show perfectly closed-loop curve as expected from the viscoelasticity effect of the epoxy adhesive [4,16,17]. The remaining strain in the stress-strain diagram does not represent the plastic deformation either.…”
Section: Methodsmentioning
confidence: 84%
“…Utilizing the bulk adhesive of a higher modulus produces stiffer and stronger adhesive joints for a given adherend [1]. Then, some researchers improves the modulus of bulk epoxy adhesives by filling the epoxy adhesive with silica particles [2][3][4]. Adhesive joints also sensitive to the loading rate [5,6].…”
Section: Introductionmentioning
confidence: 99%